[RuV(NCN-Me)(bpy)(O)]3+ mediated efficient photo-driven water oxidation. Issue 66 (28th June 2016) - Patel, Jully; Majee, Karunamay; Padhi, Sumanta Kumar
Abstract : The complex [Ru(NCN-Me)(bpy)H2 O](PF6 )2 acts as an active catalyst for the photo-driven oxidation of water, when employed with [Ru(bpy)3 ] 2+ as photosensitizer and Na2 S2 O8 as sacrificial electron acceptor at pH 6.5 phosphate buffer, with a TON of 130. Abstract : The [Ru(NCN-Me)(bpy)H2 O](PF6 )2 complex (1 ) (where NCN-Me is the neutral N -methyl-3, 5-di(2-pyridyl)pyridinium iodide after deprotonation of the C–H bond) acts as an active catalyst for the visible light driven oxidation of water, when employed with [Ru(bpy)3 ] 2+ as the photosensitizer and Na2 S2 O8 as the sacrificial electron acceptor in a phosphate buffer solution at pH 6.5, in the presence of a visible light emitting diode (LED; visible light 10.2 mW cm −2 ) at 20 °C. The system exhibits very high activity, achieving 130 turnovers with respect to catalyst and an initial turnover rate TOF of 0.10 s −1 . The controlled experiments conducted for the photo-oxidation of water indicate that the catalytic system is dependent upon the following: (i) a visible light source, (ii) photosensitizer, (iii) catalyst and, (iv) pH. During the photocatalysis of water oxidation for 2 h in a phosphate buffer solution at pH 6.5, there was no degradation of the catalyst1, which indicates the good photo-stability of the complex. The NCN-Me coordinates as a neutral ligand after deprotonation of the central C–H bond; generating the negatively charged carbon center favors a reduction in the redox potential of the complex, which considerably lowers the overpotential to 100 mV at pH 6.5 for the oxidation of water.